Exploring the SARS-CoV-2 spike protein destabilizer toxin from the scorpion, spider, and wasp group of toxins as a promising candidate for the identification of pharmacophores against viral infections - Mousa O. Germoush; Maged Fouda; Mohammad J. S. Mantargi; Moustafa Sarhan; Barakat M. AlRashdi; Diaa Massoud; Ahmed E. Altyar; Mohamed M. Abdel-Daim (Open Veterinary Journal)
Background: The SARS-CoV-2 virus is the infectious agent that causes coronavirus illness (COVID-19). The majority of virus-infected individuals will recover without the need for special care after experiencing mild to moderate respiratory symptoms. Some people, nevertheless, will get quite sick and need medical help. The choice of COVID-19 treatment should be made individually. The severity of the illness and the chance that it will worsen will determine the decision. Therefore, developing more potent medications is always a primary goal. Finding more effective drugs is a top priority. In this regard, natural animal toxins, such as toxin derived from scorpions, spiders, and wasps, have been found to include compounds that have significant therapeutic properties. Specifically, targeting the spike protein which acts as a gateway for the vires to enter the human or animal cells.